A Clinical Audit of Post-Operative Outcomes of Laparoscopic Nissen’s Fundoplication in a Single Center in Sub-Saharan Africa - Cecilia Muvenyi Munguti; Bernard Ndung’u (The Annals of African Surgery, 2024)
Introduction: Gastroesophageal reflux disease (GERD) is a common benign condition with a population prevalence of 18–28%. Laparoscopic antireflux surgery is increasingly being offered to patients with GERD in our setting; however, the outcomes remain unknown. Methodology: A retrospective clinical audit of patients who underwent laparoscopic Nissen’s fundoplication in a single center. Data were summarized as mean (±SD) and median (interquartile range [IQR]); associations were analyzed with Chi square or Fischer’s exact test. A Modified Visick scoring system was used to assess the severity of symptoms after surgery. Regression models were used to analyze the factors associated with recurrence. Kaplan–Meier plots were plotted, and cox regression models, hazard ratio, and their confidence intervals were calculated. Results: A total of 127 patients were identified, with 6 having had previous laparoscopic Nissen’s fundoplication. Post-operative modified Visick scores at 2 weeks and 3 months were 1.04(±0.05) and 1.03 (±0.04), respectively, for both typical and atypical symptoms. The recurrence rate was 12.6%, with 87.4% 5-year recurrence-free survival. Conclusion: Laparoscopic Nissen’s fundoplication provides good control of both typical and atypical GERD symptoms with a low recurrence rate and a 5- year recurrence-free survival that is comparable to universal rates.